'Coming up next': The discourse of television news headlines. (October 2016) - Montgomery, Martin; Feng, Debing
Despite the adoption of the term headline for both print news and broadcast news, their roles in the different media are not the same. Print headlines are mostly contiguous with the story to which they refer. Broadcast headlines, however, are often at some temporal distance from their associated news item. In the print medium every story carries a headline. In broadcast news only some items are headlined. And yet, whereas the linguistic properties of print headlines have been much studied, almost no attention has been given to broadcast headlines. This article uses a corpus of headlines from BBC television news to explore their discursive form and function. It isolates a basic structure of heading (+supplement) for television news headlines and delineates a repertoire of patterns through which the structure is realised. In doing so, it suggests that the core function of television news headlines is to engage with the audience by projecting aspects of their news values forward through the programme.